Globalisation and euro area trade: Interactions and challenges - Ursel Baumann; Filippo di Mauro (European Central Bank (ECB), 2007)
As a major player in world trade, the euro area is strongly influenced by globalisation, but is far from being a passive spectator. The paper analyses how the euro area's trade specialization has changed in response to stronger international competition and the emergence of new global players, evaluating results and possible challenges ahead. The message remains mixed. On the positive side, the export specialisation of the euro area is increasing in some mediumhigh or high-tech sectors where productivity growth is strong and demand robust, such as pharmaceuticals, also by a more intensive recourse to importing intermediate goods from low-cost countries. On the other hand, in comparison to other industrialised economies, the euro area has been somewhat slower in moving towards research-intensive goods and away from labour-intensive sectors. While this could reflect data classification issues, it may also be a sign of structural rigidities in the euro area, which hinder adjustment processes.
Keywords: 330; Internationaler Wettbewerb; Internationale Arbeitsteilung; Außenhandelsstruktur; EU-Staaten